A new approach to control the segregation of (Ta, W)C cubic phase in ultrafine WC–10Co–0.5Ta cemented carbides. (15th April 2015) - Li, Na; Zhang, Weibin; Du, Yong; Xie, Wen; Wen, Guanghua; Wang, Shequan
Abstract : The dispersity of (Ta, W)C cubic phase in cemented carbides is crucial for controlling the microstructural homogeneity and improving the mechanical properties. An effective method for improving the segregation of (Ta, W)C phase is presented, with a guide from the thermodynamic calculation. Ultrafine WC–10Co–0.5Ta cemented carbides with different carbon contents were sintered at 1410 °C under a vacuum. With increasing carbon content, the (Ta, W)C phase segregation was gradually eliminated, and both transverse rupture strength and hardness increase.